Design and Development of Topic-based Students’ Knowledge Modelling System using Fuzzy Set Theory and Visual Analytics - Wen Thing, Ng; Chee Siong, Teh; Chwen Jen, Chen (Science Publishing Corporation, 2018)
To the field of education, advances in technologies raise opportunities and challenges in delivering personalised learning to heterogeneous group of learners while monitoring and analysing their learning progress and learning outcomes. This paper addresses the challenges of gaining a big picture about learners’ knowledge that is essential for providing personalised learning. Next, a system that models students’ knowledge is proposed in which topic-based approach, fuzzy set theory, and visual analytics were applied to design and develop the proposed system. The proposed system was designed with the capabilities to model, analyse and report individual learner’s knowledge, whereas its applicability was presented and discussed based on a real-world case study.